SOSIALISASI KESELAMATAN DAN KESEHATAN KERJA KELISTRIKAN UNTUK MASYARAKAT DESA JELANTIK LOMBOK TENGAH - Ida Ayu Sri Adnyani; Sultan Sultan; I Made Ari Nrartha; I Made Ginarsa; Agung Budi Muljono; Ni Made Seniari (Universitas Mataram, 2022)
The community of Jelantik Village, Central Lombok Regency is one of the assisted villages of Mataram University. Based on observations, there are still many village communities who are lacking. Jelantik Village Community, Central Lombok Regency, is one of the assisted villages of Mataram University. Based on observations, there are still many village people who do not understand and use electrical equipment not in accordance with the 2011 General Electrical Installation Requirements procedures and standards. The purpose of community service is to provide an understanding of the importance of Occupational Safety and Health (HSE) applied in their respective work environments. . The method used is socialization and giving questionnaires by calculating the percentage of the Guttman scale. The Guttman scale is used to determine the percentage of understanding of the HSE electricity category. Based on the results of the tabulation, the number of socialization participants was 13 out of 20 participants invited. The age range of the participants was between 18-40 years with an average education level of high school level and one with a bachelor's degree. Questionnaire results were assessed using the Guttman scale, with a total of 56 yes answers and 48 not yet answers, so the average score was 4.3. Based on the average score, it can be determined that the percentage is 33.07% on the Guttman scale in the range of 21% -40%. These results indicate that the respondents' understanding of HSE electricity is in the weak/less category. This result is due to the lack of socialization carried out by related parties, causing a high risk of accidents such as fire.